Isolated Pulmonary Valve Endocarditis Caused by Enterococcus faecalis—Facing the Unpredictable - Andrei Vâţă; Isabela Ioana Loghin; Radu Ștefan Miftode; Daniela Crişu; Cătălina Mihaela Luca; Alin Mihai Vasilescu; Ioana Maria Onofrei; Tudorița Parângă; Ionela-Larisa Miftode (Antibiotics)
Background: Infective endocarditis is a severe, life-threatening condition which affects the endocardial lining of the heart. Right-sided IE typically affects the tricuspid valve and, less commonly, the pulmonary valve, often in association with intravenous drug use and intracardiac devices. Enterococcus faecalis, a significant pathogen in healthcare settings, is frequently resistant to several antibiotics, complicating treatment. Results: We present the case of a 69-year-old man diagnosed with isolated pulmonary valve endocarditis, with no identifiable risk factors, good oral hygiene, and no recent dental procedures. In our case, the E. faecalis strain, initially susceptible to ampicillin, acquired resistance during high-dose ampicillin and gentamicin therapy, leading to cardiac surgery and prolonged antibiotic treatment. Conclusions: IPE is rare, emphasizing the need for heightened clinical awareness and thorough diagnostic evaluation, especially in patients with endocarditis symptoms and known risk factors. Although ampicillin resistance in E. faecalis is uncommon, its emergence during treatment presents a challenge, necessitating careful antibiotic stewardship to improve outcomes.